Bulk collection : systematic government access to private-sector data - Cate, Fred H.; Dempsey, James X. (New York, NY : Oxford University Press, 2017)
This text is the culmination of a nearly 6-year project to examine the systematic government access of private information from companies and other private-sector organisations. It provides 12 updated country reports to present both descriptive and normative frameworks for analysing national surveillance laws, and to focus on international law, human rights law and oversight mechanisms.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 19, 2017).
Keywords: Government information -- Law and legislation; Electronic records -- Access control; Privacy, Right of; Data protection -- Law and legislation; Electronic surveillance -- Law and legislation; Internet -- Government policy; Data transmission systems -- Law and legislation; Law; Laws of specific jurisdictions & specific areas of law